The Structure of General Physical Fitness of Girls - Future Officers During Training at the Military Academy - Victor Sliusarchuk; Gennadii Iedynak; Oksana Blavt; Rostyslav Chaplinskyі; Lesia Galamanzhuk; Vadim Stasyuk; Olena Klius (OVS LLC, 2022)
The study objective consist in studied the structure, which marked the change in the general physical fitness of the same girls throughout the period of their studies at the military academy. Materials and Methods. The study involved 108 girls, their age at the beginning of the study was 17-18 years. Taking into account the recommendations of experts, a battery of tests was used to assess the development of basic motor skills. Testing took place at the beginning of each new school year. Results. Received evidence of this. During the training at the military academy, the general physical fitness of girls changes every year, which has its own structure with features that depend on the year of study. The first such structure is determined by static strength endurance, flexibility, speed qualities, and muscular force, during the second year of study - static strength endurance, aerobic endurance, and coordination in cyclic locomotions, during the third - flexibility, explosive force, and aerobic endurance, during the fourth - muscle strength, speed, and aerobic endurance. Conclusions. Establishing the structure of physical fitness of girls - future officers during each year of study at the military academy is an important task. To improve the general physical fitness of girls - future officers, it is advisable to design the content of the program, taking into account the results. The program should focus on the development of motor skills that form a certain structure of change in the general physical fitness of girls in a given year of study.